Workshop Membangun Perusahaan Perseorangan Untuk Usaha Bidang IT Untuk Mahasiswa Semester Akhir Universitas Bhayangkara Jakarta Raya - Munandar, Tb Ai; Handayani, Dwipa; Wulandari, Retno (Jurnal Dharmabakti Nagri, 2023)
The community service activity entitled "Workshop on Building Individual Companies for Businesses in the IT Sector for Final Semester Students at Bhayangkara University, Jakarta Raya" is a real effort to increase the knowledge and skills of final semester students in planning and managing individual companies in the Information Technology (IT) sector. This workshop aims to provide practical guidance in starting an IT company, introduce the legal aspects of IT business, and invite students to apply their knowledge in real situations. This activity covers various relevant topics, such as business planning, IT product development, financial management, marketing strategy, and legal aspects related to IT business. In addition, the workshop also involved experienced IT practitioners and entrepreneurs as guest speakers, who provided invaluable practical insights. The results of this workshop reflect an increase in participants' understanding and skills in planning and starting an IT business. Participants have a better understanding of the process of registering a private company online via the AHU website and the importance of registering for a Kemenkumham permit. This workshop not only improves conceptual understanding, but also provides practical skills that can be applied in the real world. Thus, this workshop has a positive impact on the development of entrepreneurship among final semester students at Bhayangkara University, Jakarta Raya. Furthermore, sustainability evaluations and follow-up steps are needed to ensure that the knowledge and skills acquired remain sustainable and support students in their efforts to become entrepreneurs in the IT industry.